Mineral Inventory of the Algares 30-Level Adit, Aljustrel Mine, Iberian Pyrite Belt, Portugal - Silva, Teresa (2021)
ABSTRACT: Mining activity in Algares (Aljustrel Mine, Portuguese sector of the Iberian Pyrite Belt, IPB) stems prior to Roman times. As the orebody is vertical and relatively thin, mining was carried out mainly along underground adits (galleries). Nowadays, the deposit is considered exhausted and the area is being rehabilitated for a different use. The Algares +30 level adit intersects two volcanic units of the IPB Volcano-Sedimentary Complex. The massive sulphide and related stockwork zone are hosted by the Mine Tuff volcanic unit and are exposed in the walls of the gallery, showing intense hydrothermal alteration. Along the mine adit, the geological sequence is affected by strong oxidation and supergene alteration, giving rise to the formation of secondary minerals through the oxidation of the sulphides. The most common minerals found were melanterite (FeSO4 center dot 7H(2)O) and chalcanthite (CuSO4 center dot 5H(2)O), forming essentially massive or crystalline aggregates, ranging from greenish to bluish colours. Melanterite from the walls revealed to be Cu-rich by opposition to that from stalactites/stalagmites formed below the old ore storage silo revealing the low-copper-grade ores exploited underground. The mineralogy of the efflorescent salts was used to ascertain the processes involved in their formation, and moreover, the inventory of minerals is presented, as well as their principal characteristics.